Interaction - Behney, Jennifer 1972-; Gass, Susan M. 1943- (Cambridge University Press, 2021)
This Element in the Cambridge Elements in Second Language Acquisition series examines the role of interaction in Second Language Acquisition research, with a focus on the cognitive interactionist approach. The Element describes the major branches of the field, considering the importance of conversational interaction in both the cognitive interactionist framework as well as in sociocultural approaches to second language learning. The authors discuss the key concepts of the framework, including input, negotiation for meaning, corrective feedback, and output. The key readings in the field and the emphases of current and future research are explained. Finally, the authors describe the pedagogical implications that the cognitive interactionist approach has had on the teaching of second languages
Title from publisher's bibliographic system (viewed on 15 Sep 2021)
Keywords: Second language acquisition / Study and teaching; Language and languages / Study and teaching; Social interaction; Interaktion; Fremdsprachenlernen